Η κοινωνική απόσυρση στην παιδική ηλικία: Εννοιολογικές, μεθοδολογικές και αναπτυξιακές αποσαφηνίσεις - Γαλανάκη, Ε.; Π Βογιατζόγλου (Παιδί και Έφηβος: Ψυχική Υγεία και Ψυχοπαθολογία, 2007)
In this study an attempt was made to provide conceptual, methodological, and developmental clarifications of social withdrawal in childhood. The existing research data on the various types of social withdrawal are reviewed, and several types of social withdrawal are defined. Related concepts, such as behavioral inhibition, shyness, and reticence, as well as the types of solitude (i.e., aloneness, loneliness, and constructive aloneness) are also defined. Social withdrawal is differentiated from sociometric neglect and sociometric rejection. Motivational issues (i.e., approach-avoidance) are discussed in order to achieve further definitional clarity. From a methodological viewpoint, the most frequently used techniques (observation and questionnaires for educators and peers) for the assessment of the various types of social withdrawal are reviewed, and some of their limitations are noted. Lastly, developmental clarifications are provided through a review of the extant research on the stability of different types of social withdrawal over time, their developmental trajectories, their correlates and consequences (e.g., their association with internalizing problems), possible mediator variables, and the role of gender and culture. Conclusions are drawn for the current status and for the future of research on social withdrawal in childhood.